Evaluation of the WHO/CDC Syphilis Serology Proficiency Programme to support the global elimination of mother-to-child transmission of syphilis: an observational cross-sectional study, 2008–2015 - Ellen Kersh; André O Hopkins; Thuy Trinh; Yetunde F Fakile; Allan Pillay; Melanie M Taylor; Mary Kamb (BMJ Open)
Objectives Syphilis morbidity is high among pregnant women in lower income countries with limited laboratory capacity. We evaluated a long-standing global Syphilis Serology Proficiency Programme (SSPP) that supports testing quality in national reference laboratories to determine if participation affects congenital syphilis elimination strategies.Design In this observational cross-sectional study, we calculated coverage on type, frequency and quality of syphilis testing reported by laboratories enrolled in the SSPP from 2008 to 2015. We used country-reported data to WHO on four congenital syphilis (CS) indicators and World Bank country economic data to compare coverage and completeness of reporting of indicators in lower income countries with and without an SSPP-enrolled laboratory.Participants From 2008–2015, 78 laboratories from 51 countries participated in >1 SSPP evaluation; 56% were national reference laboratories, of which most (93%) participated for >3 years and 11 (22%) in all 24 cycles.Results Median proficiency performance score was >95% regardless of test conducted. Of the 51 countries with an SSPP-enrolled laboratory, 22 (43%) were lower-income countries, of which 21 reported CS data during 2008–2015. Comparing CS data from 87 (90% of total) lower income countries with and without an SSPP-enrolled laboratory, countries with an SSPP-laboratory had stronger reporting on antenatal syphilis testing (p=0.04). For 2015, an estimated 74% of prenatal syphilis tests and 63% of positive tests reported to WHO from countries with an SSPP-enrolled laboratory.Conclusion The SSPP has focused well on national reference laboratories, but has been only partially successful in recruiting laboratories from lower income countries. The finding that over half of syphilis infections in pregnant women living in countries with SSPP-enrolled laboratories suggests wide reach of the current quality assurance programme. However, reach could expand with focussed recruitment of laboratories from lower income countries.